PERAN MEDIASI PENGUNGKAPAN EMISI KARBON TERHADAP HUBUNGAN FINANCIAL SLACK DAN NILAI PERUSAHAAN: THE MEDIATING ROLE OF CARBON EMISSION DISCLOSURE ON THE RELATIONSHIP BETWEEN FINANCIAL SLACK AND FIRM VALUE - Jao, Robert; Holly, Anthony; Mardiana, Ana; Atmakusuma, Cheryl Natasya (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
This study aims to analyze the effect of financial slack on carbon emission disclosure, carbon emission disclosure on firm value, financial slack on firm value, and financial slack on firm value through carbon emission disclosure. This research is built on stakeholder theory. This study uses a purposive sampling method in sample selection. The population used in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period, with a total sample size of 184 company data. This study uses secondary data from complete annual and sustainability reports from the Indonesia Stock Exchange (IDX) and the company's official website. This research uses path analysis. The results of this study indicate that financial slack has a positive and significant influence on the disclosure of carbon emissions. The results also show that disclosure of carbon emissions positively and significantly influences firm value. The results of this study also show that financial slack has a positive and significant effect on firm value. The results of this study also show that the disclosure of carbon emissions mediates the relationship between financial slack and firm value.